2007
DOI: 10.1287/opre.1070.0428
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Robust Network Flow and Design Under Demand Uncertainty

Abstract: We describe a two-stage robust optimization approach for solving network flow and design problems with uncertain demand. In two-stage network optimization, one defers a subset of the flow decisions until after the realization of the uncertain demand. Availability of such a recourse action allows one to come up with less conservative solutions compared to singlestage optimization. However, this advantage often comes at a price: two-stage optimization is, in general, significantly harder than single-stage optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
211
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(217 citation statements)
references
References 29 publications
(23 reference statements)
0
211
0
1
Order By: Relevance
“…Constraints (12) require that the ship capacity is obeyed. Constraints (13) impose lower and upper limits on the loading and unloading quantities.…”
Section: Loading and Unloading Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Constraints (12) require that the ship capacity is obeyed. Constraints (13) impose lower and upper limits on the loading and unloading quantities.…”
Section: Loading and Unloading Constraintsmentioning
confidence: 99%
“…That is, the set of feasible solutions can be projected onto the space of the rst stage variables. This approach was followed in [12] for a simpler two-stage robust network ow and design problem, and in [8] robust approaches were used for the two dimensional spaces (with rst stage and with rst and second stage variables) for the robust VRPTW problem, albeit the projection has not been done explicitly. In [12] it was shown that even for simple graph structures the separation of the inequalities resulting from the projection is NP-hard.…”
Section: Model Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach has been developed in [EGL97], [EGOL98]. By now a large body of elegant work exists; the approach has been refined, extended and used in many applications, see [AZ05], [BGGN04], [BGNV05], [BS03], [BPS03], [BT06]. [BBN06] presents a framework for compensating for errors that fall outside of the uncertainty region being considered.…”
Section: Robust Optimizationmentioning
confidence: 99%
“…Applications of the adjustable robust counterpart include Atamtürk and Zhang (2007) and Erera et al (2009). Unfortunately, adjustable robust counterpart models are generally NP-hard.…”
Section: Introductionmentioning
confidence: 99%